INDONESIAN CAPITAL MARKET REACTION TO THE 2024 PRESIDENTIAL ELECTION (A Study on the LQ45 Index at the Indonesia Stock Exchange) - I Ketut Yoga Pradnyana Putra; I Gde Kajeng Baskara (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The reaction of the capital market reflects how market participants respond to specific information or events, making it a crucial aspect for investors when formulating appropriate investment strategies. The presidential election is a political event that can create uncertainty and influence investors' decision-making. This study aims to analyze the reaction of the capital market to the 2024 Presidential Election (Pilpres) in Indonesia. Presidential elections are political events that can trigger uncertainty and influence investors' decision-making. This research employs an event study method with a six-day observation window: three days before and three days after the election date. The sample consists of stocks listed in the LQ45 Index on the Indonesia Stock Exchange, selected using purposive sampling. Expected returns are calculated using the mean-adjusted model, while the hypothesis is tested using the Wilcoxon Signed Rank Test. The findings reveal no significant difference in cumulative abnormal returns (CAR) before and after the 2024 Presidential Election. However, a significant difference is found in the average trading volume activity (TVA). These results suggest that the 2024 Presidential Election conveyed information deemed relevant by market participants, leading to increased trading activity. Nonetheless, the absence of significant price movement implies that the market had efficiently anticipated the political event, with the impact more reflected in trading intensity rather than stock valuation.